2012
DOI: 10.4161/biom.20379
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of biocompatible-nanohydroxyapatite crystals obtained by a modified sol-gel processing

Abstract: A modified sol-gel process for synthesizing nanocrystalline hydroxyapatite powders (nHA) for biomedical applications, using tetrahydrated calcium nitrate [Ca(NO3)2∙4H2O] and phosphorous pentoxide [P2O5] as precursor, is presented and discussed. The powders were washed and heat-treated at different temperatures and then characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The total process time reached with this modified process was less than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The TEM images demonstrated that the fibroin could direct the assembly and nucleation of HA nanocrystals along the template (Figure 10). The typical needle-like morphology of HA crystals was well represented on 3D morphologies only, with aspect ratio measurements of nanocrystals close to that of synthesized HA [43]. The SAED images indicated a polycrystalline diffractogram for braided structures [34] (Figure 10) with preferential orientation extending along the c-axis, as also confirmed from the values of intensity ratio (Figure 6).…”
Section: Discussionsupporting
confidence: 51%
“…The TEM images demonstrated that the fibroin could direct the assembly and nucleation of HA nanocrystals along the template (Figure 10). The typical needle-like morphology of HA crystals was well represented on 3D morphologies only, with aspect ratio measurements of nanocrystals close to that of synthesized HA [43]. The SAED images indicated a polycrystalline diffractogram for braided structures [34] (Figure 10) with preferential orientation extending along the c-axis, as also confirmed from the values of intensity ratio (Figure 6).…”
Section: Discussionsupporting
confidence: 51%
“…17 Nanomaterials usually show higher adsorption ability than their bulk counterparts. Nanohydroxyapatite (NHA), an important inorganic material in biology and chemistry, exhibits excellent biocompatibility and adsorption properties, 18 and has been widely used as a sorbent for the adsorption and separation of biomolecules (e.g. bovine serum albumin), 19 and for the removal of heavy metals (e.g.…”
Section: Introductionmentioning
confidence: 99%